2001
DOI: 10.1006/jpdc.2001.1747
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Routing on the New Switch Chip for IBM SP Systems

Abstract: The IBM RSÂ6000 SP is one of the most successful commercially available multicomputers. SP owes its success partially to the scalable, high bandwidth, low latency network. This paper describes the architecture of Switch2 switch chip, the recently developed third generation switching element which future IBM RSÂ6000 SP systems may be based on. Switch2 offers significant enhancements over the existing SP switch chips by incorporating advances in both VLSI technology and interconnection network research. One of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…n the number of nodes in the network 1 . This interval is valid for all the ascending links of the switch and can result in a cyclic interval.…”
Section: Adaptive Routing Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…n the number of nodes in the network 1 . This interval is valid for all the ascending links of the switch and can result in a cyclic interval.…”
Section: Adaptive Routing Implementationmentioning
confidence: 99%
“…Remember that FIR implements the routing function. In [1], the authors compare several selection functions for adaptive routing, but they only consider the peak throughput in the evaluation, so they conclude that selection function is not critical. However, in [6], several selection functions for fat-trees were proposed and the authors notice that selection function has a high impact over average latency.…”
Section: Network Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of work has shown that AR will offer superior performance compared to deterministic and oblivious routing for many non-uniform traffic scenarios. The evaluation work herein has mainly been conducted as simulation studies [1], [9], [14], [17], [18], [24], [25], [28]. On the contrary, there are also contributions revealing that deterministic routing (DR) for some scenarios and topologies, such as Fat trees, achieve a similar, or even a higher throughput than AR.…”
Section: Introductionmentioning
confidence: 99%
“…In source routing, the source node computes the path prior to packet injection and stores it in the packet header, which may noticeably increase the packet header length. Source routing has been used in some networks because routers are very simple [8,15]. In this routing scheme, the switches of the network just read the stored route in the packet header and forward the packet through the indicated output port, which makes routing very quickly and switches very simple.…”
Section: Routing Algorithms Taxonomymentioning
confidence: 99%